Quina Retouch Does Not Maintain Edge Angle Over Reduction. (2nd January 2021) - Lin, Sam C.; Marreiros, João
ABSTRACT: The Quina scraper features an important role in the discussion of European Middle Palaeolithic variability. Explanations for its characteristic retouch and blank morphology have ranged from economic to functional and cultural considerations. One hypothesis is that Quina retouch maintains the edge angle of the retouched margin, allowing the upkeep of high cutting potential despite repeated resharpening. In this study, we examine this hypothesis by using a sample of scrapers from the Middle Palaeolithic site of Roc de Marsal in southwest France. The results show that, when the influence of reduction intensity and flake thickness are controlled, Quina retouch has no detectable impact on the retouched edge angle. Instead, the overall higher edge angles among Quina scrapers are a product of continuous reduction and the use of thicker blanks. We discuss possible factors underlying the occurrence of Quina retouch with respect to lithic economy and function.